Compact and efficient Er-Yb-doped fiber amplifier - Dimyati, Kaharudin; Harun, Sulaiman Wadi; Muhd-Yassin, Shahrin Zen; Abd-Rahman, Mohd Kamil; Ahmad, Harith (World Scientific Publishing, 2008)
A compact and efficient optical amplifier is demonstrated using an erbium-ytterbium-doped fiber amplifier (EYDFA) with a double-pass configuration. It uses only 3 m of doped fiber with 20 mW pump power. This forward-pumped amplifier achieves a maximum low signal gain of 37 dB and a corresponding noise figure of 5.5 dB. Compared with the backward-pumping double-pass EYDFA, the gain obtained is 7 dB higher, with a lower noise figure of 5.5 dB. In addition, the gain obtained in this study is 17 dB higher than that of a conventional forward-pumping single-pass amplifier, while its noise figure is only 0.5 dB higher. These results show that the forward-pumped double-pass design holds great promise in the development of practical and cost-efficient optical amplifiers which can be pumped by using LEDs or low cost laser diodes.